Motivating students with learning disabilities to read - Wei, Yan; Spear-Swerling, Louise; Mercurio, Mia (Intervention in School and Clinic, 2021)
Students may lack the motivation to read for many reasons, including inadequate access to interesting texts, limited encouragement to read for pleasure from adults, instructional practices that do not foster engagement in learning, or a history of reading failure. This article focuses on students with reading disabilities who may have a long-standing dislike of reading born of repeated negative experiences with learning to read. Motivating these students to read for pleasure may seem like an unattainable goal. However, past difficulties in reading do not necessarily mean that children will dislike reading forever. In conjunction with appropriate academic interventions, student interest in reading might be improved by motivational interventions aligned with a theoretical framework discussed in this article: (a) choosing interesting texts to read, (b) stimulating knowledge-based interest, and (c) enhancing task-based interest.
Keywords: dept.sed; peer-reviewed